Sport-specific crossover point differences during a maximal oxygen consumption test - Stanzione, J. R.; Brooks, G. A.; Bruneau Jr., M. L.; French, D. N.; Nasser, J. A.; Smith, S. A.; Volpe, S. L. (Translational Journal of the American College of Sports Medicine, 2022)
Introduction/Purpose: The crossover point occurs during exercise when one transitions energy substrates from fat to predominance. The crossover point varies in an intensity-dependent manner; however, less is known about its specificity in sports with varying metabolic demands. The purpose of our study was to determine if various sports yield differences in the time to crossover and heart rate and percentage of maximal oxygen consumption (VO2max) at crossover during a standardized exercise protocol. Methods: A total of 77 athletes (39 women, 38 men; 39.1 ± 10.4 yr of age) were measured for respiratory exchange ratio during a modified Taylor VO2max treadmill test. Sports included running (n = 20), triathlon (n = 20), rowing (n = 20), and CrossFit (n = 17). A one-way ANOVA determined differences in time to crossover. A Kruskal-Wallis test was applied to determine differences between sport types for percent VO2max and heart rate at crossover. Bonferroni correction procedures were used to control the family-wise error rate and maintain alpha levels at P < 0.05. Results: Average time to crossover for all athletes was 3:43 ± 1:12 min. Times to crossover for runners, triathletes, rowers, and CrossFit athletes were 4:16 ± 0:58, 3:28 ± 1:08, 4:00 ± 1:23, and 3:01 ± 0:58 min, respectively. Significant differences were observed between groups for time to crossover (P = 0.007) and percent VO2max at crossover (P = 0.01). Pairwise analyses revealed that runners had a significantly longer time to crossover compared with CrossFit athletes (P = 0.009). Triathletes` percent VO2max at crossover was significantly lower than rowers (P = 0.04) and runners (P = 0.04). Conclusions: We found significant differences in time to crossover between runners and CrossFit athletes, which suggests that substrate use may be dependent on sport type.